2000
DOI: 10.1002/(sici)1096-8652(200002)63:2<68::aid-ajh2>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Splenic function in sickle cell anemia patients in Qatif, Saudi Arabia

Abstract: A prospective study was conducted to study the splenic function among sickle cell anemia (SCA) patients in Qatif (Eastern Province of Saudi Arabia). Seventy-seven patients (30 children and 47 adults aged 2-57 years) were included. (99m)Tc stannous colloid liver-spleen scan was done for each patient during steady state. The splenic function was graded from 0 to 4 in relation to liver uptake. Seventy percent of our patients showed evidence of splenic hypofunction, and most of them (83%) had severe hyposplenism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
1
11
1
Order By: Relevance
“…Nevertheless, patients differ from African Americans phenotypically and have fewer episodes of stroke, priapism, and leg ulcers and a higher prevalence of splenomegaly. 14,[70][71][72] This might be related to differences in HbF levels or coinheritance of ␣-thalassemia.…”
Section: Southwestern Provincementioning
confidence: 77%
“…Nevertheless, patients differ from African Americans phenotypically and have fewer episodes of stroke, priapism, and leg ulcers and a higher prevalence of splenomegaly. 14,[70][71][72] This might be related to differences in HbF levels or coinheritance of ␣-thalassemia.…”
Section: Southwestern Provincementioning
confidence: 77%
“…Most children with AI haplotype SCD maintain near normal splenic function compared with African haplotype patients who commonly have early auto‐splenectomy; this is probably related to the sustained high HbF in this population (Al‐Awamy et al , ; Mallouh et al , ; Babiker et al , ; Al‐Jam'a et al , ; Adekile, ; Alsultan et al , ). Persistent splenomegaly and hypersplenism sometimes require splenectomy (Mallouh & Salamah, ; Al‐Salem et al , ; Al‐Salem, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sickle cell anemia is one of the most common hereditary blood disorders in Saudi Arabia and it occurs in two different forms, one form in South West of the country is similar to the African type and the other type in the Eastern province is considered to be less severe [25]. In the Eastern province of Saudi Arabia SCA is common with sickle cell trait [26]. The current study showed that the patients who were affected with sickle cell anemia were from different Saudi Arabia areas; Eastern Saudi Arabia is the least number of affected patients (1.5%) followed by Asseer; affected patients constituting (16.4%) and from Gaizan representing (82.1%) of the total sample 67 (100%).…”
Section: Discussionmentioning
confidence: 66%